Macroprocess 11 Financial Management - Organizational Design Division (Carlos Figueroa Picado, 2020)
The Macroprocess 11 Financial management aims to " Ensure the effective and transparent use of financial resources by defining, executing and verifying guidelines and providing financial and accounting services, ensuring that all objectives are achieved". Scope: Hemispheric level. Technical and regulatory actions. Centralization at strategic levels and at Headquarters. Partially decentralized at the tactical and operational level, per region and per country